Bridging service gaps in Muslim friendly adventure tourism: stakeholder perspectives and framework development - Mazli, Muhammad Haniff Najmi; Md Sawari, Siti Salwa (Khwarezm Publication, 2025)
This study explores the needs of Muslim travellers in adventure tourism to develop a conceptual framework for Muslim-friendly experiences. Using mixed methods, it engages travellers, operators, and communities. The research promotes halal-friendly, culturally sensitive tourism that enhances regional inclusivity, supports small tourism enterprises, and fosters sustainable development. The findings offer practical solutions to strengthen regional economies and reduce poverty through inclusive adventure tourism in line with global development goals.